Evaluating the effectiveness of mulching for reducing soil erosion in cut slope and fill slope of forest roads in Hyrcanian forests - Solgi, Ahmad (Array, 2021)
Forest operations often enhance runoff and soil loss in roads and skid trails, where cut slopes and fill slopes are the most important source of sediment. This study evaluated the effectiveness of four erosion control treatments applied to cut slope and fill slope segments of forest roads of different ages in the Hyrcanian forest in northern Iran. The treatment combinations, each replicated three times, included four classes of mulch cover (bare soil [BS], wood chips cover [WCH], sawdust cover [SC], and rice straw cover [RSC]), two levels of side slope (cut slope and fill slope), two levels of side slope gradient (20–25% and 40–45%), and three levels of road age (three, 10 and 20 years after construction). Mulch cover treatments significantly reduced average surface runoff volume and sediment yield compared to BS. Regardless of erosion control treatment, greater surface runoff volume and soil loss under natural rainfall occurred on steeper slope gradients in all road age classes and decreased with increasing road age on both slope gradients. On cut slopes, average runoff and soil loss from the plots covered with WCH (17.63 l per plot, 2.43 g m–2) was lower than from those covered with SC (22.81 l per plot, 3.50 g m–2), which was lower than from those covered with RSC (29.13 l per plot, 4.41 g m–2 and BS (34.61 l per plot, 4.94 g m–2). On fill slopes, average runoff and soil loss from the plots covered with WCH (14.13 l per plot, 1.99 g m–2) was lower than from plots covered with SC (20.01 l per plot, 3.23 g m–2), which was lower than from plots covered with RSC (24.52 l per plot, 4.06 g m–2) and BS (29.03 l per plot, 4.47 g m–2). Surface cover successfully controlled erosion losses following road construction, particularly on steep side slopes with high erosion potential.